Diversity of air-borne mycoflora from indoor environment of library - Turkel Ayesha; Bhajbhuje MN (International Journal of Life Sciences, 2017)
Aeromycoflora from Library is known to be significant in respect to allergies and also involve in deterioration of cellulosic and non-cellulosic library materials. Airborne fungal flora of the Central library of R.T.M. Nagpur University Campus, Nagpur have been isolated at regular intervals for a month employing gravity plate exposure technique. Altogether 1595 colonies categorized under 23 genera and 39 species were isolated. Deuteromycota exhibited greater count of isolates with higher incidence followed by Ascomycota. Member of Basidiomycota did not persist. Cladosporium dominated the air of library exhibiting significant incidence. Aspergillus was recorded with greater count of species whereas Botrytis, Chaetomium, Cladosporium, Cunninghamella, Drechslera, Nigrospora, Phoma, Phytophthora, Pyricularia, Pythium, Rhizopus, Torula, Trichoderma and Trichothecium were encountered on agar jelly with individual species.